Quantifying the health impact of food interventions: Revisiting the Disability-Adjusted Life Years Approach - Lenaerts, Bert (2025)
Food interventions like industrial fortification and biofortification through crop breeding can help shift towards improved healthy diets, marking a significant stride in public health. Crop breeding contributes to a stable and healthy food supply by boosting agricultural yields and the micronutrient content of staples, which is pivotal for combating chronic and hidden hunger, especially in rural areas. Fortification enhances healthy diets by adding essential vitamins and minerals to commonly consumed foods, helping prevent nutrient deficiencies and support overall well-being. The burden of hunger and its consequences on health are increasingly quantified using the Disability-Adjusted Life Years (DALYs) approach, which merges years of life lost and years lived with disability, offering a comprehensive view of health impacts and aiding in resource allocation. A practical formula for quantifying the health impact of biofortification was introduced by Stein et al. (2005) and Zimmermann and Qaim (2004). This entails calculating the efficacy or relative reduction in hunger burden based on the current and post-intervention nutrient intake against the recommended dietary allowances. As data on consumption and recommended intake levels are variable and not robustly available, this paper proposes relying on relative estimates to bridge the data gaps and uncertainties, thus streamlining the quantification of fortification’s and biofortification’s impact on diets and overall health.